A New Training for Older Adults Using Combined Neuromuscular Electrical Stimulation and Volitional Contraction: A Pilot Study - SHIBA, NAOTO; OMOTO, MASAYUKI; MATSUSE, HIROO; TSUKADA, YUUYA; HASHIDA, RYUKI; TAKANO, YOSHIO (Kurume medical journal, 2016)
The hybrid training system (HTS) resists the motion of a volitionally contracting agonist muscle using force generated by its electrically stimulated antagonist. We have developed a new training method using the principle of HTS. This study was designed to evaluate the effect of HTS with electrical stimulation on muscle strength and physical function by comparing it against training without electrical stimulation in older adults. 16 subjects were randomly divided into two groups: the squat and single leg lift training (control, CTR) group, and the CTR with HTS training group. Some electrical stimulation was applied to the quadriceps and hamstring muscles in the HTS group. The subjects performed training for 25 min per session 3 times a week for 12 weeks. At points before and after the research maximal isokinetic torque, knee-flexors (KFT) and knee-extensors (KET), a one-leg standing test (OLT), a functional reach test (FRT), a 10-meter maximal gait time (10MGT) and Timed up & go test (TUG) were conducted. None of the subjects had any injuries during the study period. TUG significantly improved after the training period in both the HTS group (7.15 sec to 6.01 sec P = 0.01) and in the CTR.